"life's first need is for us to be realistic" and other reasons for examining the sociocultural construction of race in the science performance of African American students. Issue 1 (6th December 2012) - Mutegi, Jomo W.; Parsons, Eileen Carlton; Carlone, Heidi B.
Abstract The body of research aimed at explaining the science teaching and learning of African Americans has identified myriad factors that correlate with African American's science career choices and science performance generally. It has not, however, offered any satisfactory explanations as to why those factors are disproportionately racially determined. This article argues that the sociocultural construction of race, which has roots in antebellum Western society, has endured to the present day; and that there is sufficient historical tradition and empirical evidence to warrant a research agenda that accounts for the sociocultural construction of race in explaining African American science education. The article concludes by suggesting a set of research questions and theoretical perspectives that considers the sociocultural construction of race to guide future research. © 2012 Wiley Periodicals, Inc. J Res Sci Teach 50:82–103, 2013